Simulções de fusões no mercado brasileiro de refrigerantes - uma análise 1991 - 2009 - Oliveira, Beatriz Passos Theophilo Gaspar de (2010)
This work has as general objective identifying rivalry characteristics among the main firms of the brazilian soft drinks market, those firms are Coca-Cola Co, AmBev – American Beverages and “tubaínas”, products that make the competitive fringe of this industry. Therefore, this research points out the market competitive features through a historical analysis of the period from 1991 to 2009, it also exposes a short literature revision about Fusion and Acquisition concepts, and it shows and uses PCAIDS (Proportionately Calibrated Almost Ideal Demand System) model as a tool of fusion simulation between firms, facing an concentration act assumption. This research suggests that “tubaínas” seems to be closer substitutes to Coca-Cola Co brands, than to AmBev products, pointing out a greater rivalry with the first firm than with the second one.